Racism in Harper Lee’s To Kill A Mockingbird - Harianto Andri; Yohanes Tuaderu (LINGUA LITERA : journal of english linguistics and literature, 2019)
This article presents Harper Lee’s concern on racism reflected in the novel To Kill A Mockingbird. This research aims to scrutinize the view point of the main character – Scout – about racism. There are two problems to discuss: first, the society’s influence to the development of racism, and second, the social relation between Whites and Blacks. The discussion is begun with the description of the social conflict in America in 1930s at a glance using habitus theory and symbolic violence by Pierre Bourdieu. Habitus theory is used to analyze the influence of society to the emergence of racism, and the symbolic violence is used to highlight the social relation of whites and blacks. The analysis is conducted by applying library research method to collect information and data related to the discussion. After finishing the research, the writers find that the social condition in 1930s supported the growth of racism in Southern part of the USA. The great depression in economic field also made racism grew faster. Consequently, the blacks became the victims of white prejudice and discrimination.